Reflection on interdisciplinarity in promoting the mental health of teachers in higher education (Research, Society and Development, 2022)
Objective: To reflect on the interdisciplinarity in the promotion of teachers' mental health and the challenges faced in the teaching practice of higher education. Methodology: Bibliographic research with searches in the bases: Scientific Electronic Library Online; Virtual Health Library (BVS) and on the World Health Organization website. Results: Health Promotion is essential for students to be able to develop skills and abilities to deal with these contemporary challenges as future professionals. Therefore, there is a need to train higher education institutions with personal, social, strategic, creative, critical and leadership skills, aiming at the ability to make decisions with assertive behaviors. Discussion: Mental health, given its breadth, allows the development of social identity and autonomy in life. The provision of services by various professionals in health and education institutions is evident in everyday life, thus promoting the distribution of multiple functions and professions. Final considerations: The need to promote continuing education actions focused on promoting health education in higher education is perceptible. As well, it is essential that interdisciplinary projects are created that favor the continuous integration between education and health, in order to promote quality of life, especially with a focus on mental health.